Genetic Structure in Populations of Euterpe precatoria Mart. in the Brazilian Amazon - Ramos, Santiago Linorio Ferreyra; Dequigiovanni, Gabriel; Lopes, Maria Teresa Gomes; Aguiar, Ananda Virginia de; Lopes, Ricardo; Veasey, Elizabeth Ann; Macêdo, Jeferson Luis Vasconcelos de; Alves-Pereira, Alessandro; Fraxe, Therezinha de Jesus Pinto; Wrege, Marcos Silveira; Garcia, José Nivaldo (Frontiers in Ecology and Evolution, 2021)
Euterpe precatoria is a palm tree belonging to the Arecaceae family, occurring in Western and Central Brazilian Amazonia. Its fruit, which is very appreciated in the Amazon region, produces pulp that is consumed in fresh form. Its production is carried out almost exclusively by extractive farmers. In order to establish adequate strategies to sustain this genetic resource, we need knowledge about the diversity and genetic structure in natural populations. This study aimed to evaluate the influence of geographic distance on genetic structure in the main extractive populations of E. precatoria in the Brazilian Amazon. Leaves from 377 plants were collected in 19 populations located in 16 municipalities in the State of Amazonas and three in the State of Rondônia. Twelve microsatellite loci were used to genotype the plants. The diversity and genetic structure among populations were estimated. The average number of alleles per locus was 5.97. The observed heterozygosity means (HO) were higher than expected (HE) at the population level (HO = 0.72, HE = 0.66) and fixation index (f = -0.100) was negative. The FST value (0.1820) and the AMOVA results (Φ = 0.1796) showed population structure. The populations were clustered into three groups (K = 3) in the Bayesian analysis. The Discriminant Analysis of Principal Components (DAPC) confirmed eight clusters, with the populations close to those identified by the Bayesian analysis. The geographic differentiation was confirmed by the groupings obtained in the Structure analysis and the DACP function. Information related to phenotypic, genetic and environmental characterization of populations is important to guide conservation and management strategies and the formulation of public species management policies in Amazonia.